The Greater Awyu Languages of West Papua - Vries, Lourens de (Pacific linguistics ;, 2020)
This book is a comprehensive and authoritative description of the Greater Awyu family of Papuan languages. The book brings together many decades of research on Greater Awyu languages, including 10 years of field work by the author. The book presents a description of major patterns found in languages of the family: phonology, morphology, syntax and discourse. In addition, major aspects of the anthropological linguistics of Greater Awyu languages are described: counting systems, language names, kinship, linguistic ideologies, lexical substitution registers, avoidance and taboo. The linguistic patterns of Greater Awyu languages are systematically placed in the genetic, typological, areal and historical contexts of New Guinea. The long dialect continuums within the family, by reflecting different diachronic stages, offer a window on the origin of switch reference, clause chaining, topic markers, postpositions and double-headed relative clauses. The book is relevant for readers interested in the typological, historical and cultural linguistics of New Guinea but also for anthropologists and historians because the history and cultural practices of Greater Awyu speakers are a key part of the story of this language family.